2020
DOI: 10.1186/s40478-020-00928-3
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal granule cell dispersion: a non-specific finding in pediatric patients with no history of seizures

Abstract: Chronic epilepsy has been associated with hippocampal abnormalities like neuronal loss, gliosis and granule cell dispersion. The granule cell layer of a normal human hippocampal dentate gyrus is traditionally regarded as a compact neuron-dense layer. Histopathological studies of surgically resected or autopsied hippocampal samples primarily from temporal lobe epilepsy patients, as well as animal models of epilepsy, describe variable patterns of granule cell dispersion including focal cell clusters, broader thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 61 publications
0
45
0
Order By: Relevance
“…They might, however, be useful as a model to interpret the role of an inflammatory state in the brain, possibly favoring the development of epilepsy. In this context, it should be noted that Roy et al (2020) , who recently reported on GCD as a non-specific finding in pediatric patients, did not observe a microglia reaction in the analyzed hippocampal tissue with no history of seizures. This finding, together with our observation of microgliosis after heat-shock, underpins the importance of microgliosis as an important parameter to distinguish pathological from non-specific granule dispersion.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…They might, however, be useful as a model to interpret the role of an inflammatory state in the brain, possibly favoring the development of epilepsy. In this context, it should be noted that Roy et al (2020) , who recently reported on GCD as a non-specific finding in pediatric patients, did not observe a microglia reaction in the analyzed hippocampal tissue with no history of seizures. This finding, together with our observation of microgliosis after heat-shock, underpins the importance of microgliosis as an important parameter to distinguish pathological from non-specific granule dispersion.…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, recent retrospective studies on hippocampi of pediatric patients with or without seizure history did not show significant differences of cell loss or GCD ( Harding and Thom, 2001 ; Roy et al, 2020 ). In addition, abnormal neuronal stratification and microgliosis were also observed in the hippocampus of seizure-free individuals, suggesting that GCD cannot be considered to be pathognomonic for TLE ( Roy et al, 2020 ), much in contrast to earlier studies which had judged GCD to be a specific histopathological feature of TLE ( Lurton et al, 1997 ; Koyama et al, 2012 ; Thom, 2014 ). Febrile seizures and ectopic granule cell positioning were hyperthermia-induced in rats in vivo ( Koyama et al, 2012 ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Observational and experimental protocols designed to evaluate GCL alterations are necessarily biased toward hippocampal sampling which might account for a trend toward increased sensitivity to over-interpret normal anatomic variants in some cases as the spectrum of normal variant anatomy during hippocampal development is poorly defined and prevalence data for the general pediatric population are lacking. A recent morphometric analysis of archived autopsy pediatric material found no correlation between GCD and seizure history (54). Thus, the significance of GCL alterations remains uncertain.…”
Section: Neuropathologic Findings In Sudcmentioning
confidence: 99%